Evidence-Based Class Literacy Instruction for Children With Speech and Language Difficulties. Issue 4 (October 2020) - Gillon, Gail; McNeill, Brigid; Denston, Amanda; Scott, Amy; Macfarlane, Angus
Abstract : This study investigated the response to class-wide phonological awareness and oral language teaching for 40 children who entered school with speech and language difficulties. A stepped wedge research design was adopted to compare the immediate impact of the 10-week teacher-led instruction. The progress of the children with speech and language difficulties was monitored over the first school year and compared with 110 children with language difficulties alone and 95 children with typical development. Children with speech and language needs showed a strong intervention response in phoneme awareness and vocabulary learning but needed more support to transfer skills to word decoding and spelling. Implementing the approach earlier in the school year resulted in stronger literacy performance at the year-end for all three groups. The importance of positive speech–language pathologist and teacher collaborations to support a systematic approach to evidence-based foundational literacy teaching is discussed.